Natural Rubber Latex: Study of a Novel Carrier for Casearia sylvestris Swartz Delivery. (12th February 2014) - Azevedo Borges, Felipe; Cesar Bolognesi, Luis Felipe; Trecco, Alberto; de Camargo Drago, Bruno; Baldo de Arruda, Larisa; Noronha Lisboa Filho, Paulo; Gonçalves Pierri, Elaise; de Oliveira Graeff, Carlos Frederico; Gonzaga dos Santos, André; Romeiro Miranda, Matheus Carlos; Donizetti Herculano, Rondinelli
Abstract : Natural rubber latex (NRL) from Hevea brasiliensis has showed interesting biomedical properties as improving wound healing, cell adherence, tissue formation, and angiogenesis. It is used for biosynthesis of nanoparticles, sensors and prosthesis and for drug delivery systems (for drugs, plant extracts, and nanoparticles). To enhance its wound healing properties was incorporated Casearia sylvestris Swartz extract, whose pharmacological activity includes anti-inflammatory, analgesic, antiseptic, antiulcer, and antitumor due to its casearins and phenols. Results showed the prolonged release of its compounds (35 days) and the mechanism of release is super case II (n > 1 ) by Korsmeyer-Peppas model. Although SEM shows different sizes of clusters at the surface, the release is homogeneous through the biomembrane. FTIR shows no interaction between the matrix and the extract, with computation of the presence of some casearins.